Spatial Patterns in Nutrient and In Vivo Fluorescence Distributions in the Marginal Ice Zone and the Seasonally Open Oceanic Zone in the Indian Sector of the Antarctic Ocean, in Austral Summer - Odate, Tsuneo; Hirawake, Toru; Tanimura, Atsushi; Fukuchi, Mitsuo (2000)
Surface temperature, salinity, concentrations of silicate (Si) and nitrate + nitrite (N), and in vivo fluorescence (Fluor) were investigated in the marginal ice zone (MIZ) and the seasonally open oceanic zone (SOOZ) (32–40°E, 64–69°S) from February 23 to 28 1992. In the MIZ the mean Si and N were 67.8 ± 2.2 μM and 32.5 ± 1.7 μM, respectively. There was a trend that low N values coincided with high Fluor values. Observation conducted at one point (64°S, 38°E) revealed a diel variation pattern in Fluor. Applying this pattern of deviation from noon value, all Fluor data were normalized to value at local noon. In the MIZ a significant negative correlation was observed between the normalized Fluor and N but not Si. On the other hand, Si decreased continuously from south to north in the SOOZ and was negatively correlated with the normalized Fluor. Difference in Si concentration was about 30 μM between the sea around 64°S and the MIZ, while the difference in N concentration was estimated as less than 10 μM. If diatoms take up silicate and nitrogen at an approximate ratio of 1:1, additional nitrogenous nutrients other than nitrate and nitrite (e.g. ammonia, urea etc.) would be required. In this case, an f-ratio of lower than 33% is obtained. It is suggested that in the MIZ abundance of phytoplankton community dominated by non-diatom increases utilizing nitrate while in the SOOZ abundance of phytoplankton community dominated by diatoms increases consuming Si and regenerated nitrogen. journal article